Experimental analysis on active bandwidth estimation tools for clink, bing, stab for mesh wireless local area network - Nik Zatizzahraa, Nik Zamry (2014)
Available bandwidth – as well as capacity or achievable bandwidth – on a path or a link is one of the very important parameters to measure or estimate in a network: it is of high interest for many networking functions (routing, admission and congestion control, load balancing, etc). The bandwidth measurement techniques can be divided into two type which were active and passive measurement technique. Active measurement techniques provide the easiest and the more flexible approach, for estimating available bandwidth. In addition, they can be used for different network technologies or structures. Many techniques and tools for available bandwidth estimation appeared recently, but little attention has been given to the accuracy of the estimated values in the real Internet, most of previous studies focusing on validating the accuracy of these tools on local platform. WLAN offers wireless network communication over short distances using radio or infrared signals instead of using traditional network cabling. Therefore, this paper evaluates more about analysing bandwidth estimation in mesh wireless local area network (WLAN) using three selected active bandwidth estimation tools. This paper then discusses the results we got in different environments with different active tools. The results were discussed based on three aspects which were accuracy, consistency and failure pattern. They were tested in two different network environments: optimum network (network without external traffic) and network with external traffic. In order to carry out the testing, one access point, two access points with same bandwidth and two access points with different bandwidth were used in both network environments.